Effect of Biogas Plant Residues on Nutrient Uptake by Amaranth (Amaranthus tricolor L.) (Chittagong University Journal of Biological Sciences, 2024)
A pot experiment was conducted in the research field of the Department of Soil Science, University of Chittagong to study the effect of biogas plant residues (BPR)and NPK fertilizers on nutrient uptake by amaranth (Amaranthus tricolor L.). Six treatments having three replications were as follows:T1=Control (No BPR+No inorganic fertilizers),T2= N156P36 K80 kg ha-1 from inorganic fertilizer (recommended dose),T3-BPR 20 tha-1test from inorganic NPK fertilizer,T4=BPR 15 t ha-1+ rest from inorganic NPK fertilizer, T5-BPR 10 t ha-1+ rest from inorganic NPK fertilizer,T6-BPR 5t ha-1+ rest from inorganic NPK fertilizer.The results showed that application of biogas plant residues and inorganic NPK fertilizers significantly increased nutrient uptake byamaranth compared to control. The values of uptake of N, P, K,Ca, Mg, and Na were 4.61-38.85,0.55 -3.36, 3.56-45.76,0.93 -6.09,1.25-8.56 and 0.17-0.99 mg plant-1in shoot and 1.54-12.51, 0.31-1.36,1.92-17.34,0.16- 0.95 and 0.22-1.33 and 0.05-0.85 mg plant-1 in root, respectively. Nutrient uptake was the lowest in control,higher in the treatment of chemical fertilizer alone and the highest in the treatments of biogas plant residues in combination with chemical fertilizers except Ca uptake in shoot. Overall, application of biogas plantresidues at the rate of 5 ton ha-1 along with calculated amount of NPK fertilizer (T6) showed the best results.The Chittagong Univ. J. B. Sci. 9(1&2):81-88,2019